Harvesting of pedal power for battery charging : generation, conditioning and its measurement through non-contact means - Hafiz, Umair Ahmed Khan (Kulliyyah of Engineering, International Islamic University Malaysia, 2015)
Energy harvesting from sources such as light, wind, temperature gradient, vibration and other similar means of energy has been the focus of research these days. This research presents a new way of harnessing energy from the vehicles passing over a ramp. Basically, it is the potential energy used for generating electricity. Unlike the many other designs for power generation, this research presents the method of converting the rotational energy using a flywheel and gear mechanism into DC Power output. The conversion mechanism consists of a rack underneath the road surface at the point of road where a speed-breaker is raised. The linear motion of a rack due to the load of a passing vehicular is converted into rotational motion to run an alternator. The system is described in terms of its working principle along with the dimensions of the rack and one-way clutch assembly and the gears mechanism. The pulley structure is geared such that it is ultimately making a generator to rotate for producing an output voltage. The output voltage is of variable nature depending on the traffic flow and in which the output is later stabilized and boosted using a DC-DC converter. In this research work, a non-contact sensing technique has also been utilised to measure the generated output voltage. The experimental setup of the system is studied by experimental data obtained from two different vehicles passing by over the ramp with a known interval. The output power is estimated as every passing vehicle is contributing a certain amount of energy in a given time interval. The potential application of the resulting DC Power output could be for applications of charging battery packs of an Uninterrupted Power Supply system. That could be used for powering any emergency loads such as lights of signboard in the case when the main supply gets interrupted.